Analysis of Swear Words in Kohei Horikoshi's Anime Boku no Hero Academia Season 2 : (Pragmatics Study) - Indrowaty, Sri Aju -; Styasari, Ava Silvi (Universitas Brawijaya, 2024)
Japan is a country that is often talked about by various other countries. Things that do not escape the conversation of people from various countries about Japan are the development of technology and culture. One of the Japanese cultures that has successfully entered Indonesia is Anime. According to Napier (2005, p. 4), Anime is a term used to refer to animated films originating from Japan. Anime is an abbreviation of the word animation in English. The pronunciation of animation in Japanese turns into animation and from that mention, it is then shortened to the word anime. The purpose of this study is to describe the function and form of swear words found in Anime Boku no Hero Academia season 2. The method used in this research is a descriptive qualitative method with note-taking technique. From the research conducted, it was found that the Expletive function was 26 words, the Abusive function was 78 words, the Humorous function was 5 words, and the Auxiliary function was 4 words. With the form of circumstances as many as 71 words, animals as many as 3 words, subtle creatures 1 word, objects 8 words, body parts 6 words, kinship 7 words, activities 13 words, and professions as many as 4 words. This research is expected to add to scientific references, especially in the field of pragmatic linguistics.